A rare case report of Solitary Forehead Neurofibroma in a 19-Year-Old Female (Bangladesh Journal of Medical Science, 2026)
Background Neurofibromas are benign peripheral nerve sheath tumors that may present as solitary lesions or as part of neurofibromatosis type 1 (NF1). Solitary neurofibromas of the forehead are uncommon and can be mistaken for other soft tissue masses, delaying diagnosis and treatment. Case Presentation A 19-year-old female presented with a painless, slowly enlarging left forehead swelling since four years. Clinical examination revealed a 3 X 2 cm, firm, mobile, non-tender subcutaneous mass with intact overlying skin. Excisional biopsy was performed; histopathology confirmed a neurofibroma. The patient had an uneventful recovery and remained free of recurrence after 12 months. Conclusion Solitary forehead neurofibroma should be included in the differential diagnosis of chronic forehead swellings. Accurate preoperative assessment, careful surgical planning to preserve cosmesis, function and a histopathological confirmation are essential. Long-term follow-up is recommended to detect recurrence or new lesions.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S363-S368